Development of tourism environmental management in Kazakhstan based on successful international experience - Pazylkhaiyr, B.; Assipova, Zh.M.; Bertocchi, D. (BUKETOV BUSINESS REVIEW, 2023)
Object: The aim of this research is to analyze the best examples of international experience in tourism environmental management and the possibilities of using them in the Kazakhstan example. Methods: Several methods as comparison, analyzing case studies, and theoretical literature review have been used during the research. Findings: The authors show that Kazakhstan meets difficulties with tourism environmental management, even though it has a great potential to be one of the world leaders in this field. Consequently, the authors recommend several directions on how Kazakhstan tourism environmental management should be developed through international experience. Conclusions: The article defines the approaches that some of the developed and developing countries, which have improved the tourism industry through the environmental management tools such as, Australia (DEC), UK (win-win development), New Zealand (Marine Mammals Protection Act), Canada (Tourism Destination Model), Ecuador (Tourism associations), Costa Rica (tourism environmental management strategy), and Botswana (the community — based ecotourism). As a result, Kazakhstan can easily use all these approaches to develop its tourism environmental management.